MODERN IT TOOLS SUPPORTING INDIVIDUAL TOURISTPROJECTS - Bolek, Cezary; Papińska-Kacperek, Joanna (European Scientific Journal, ESJ, 2014)
IT tools supporting individual tourist projects are taken into consideration in this paper. The concept of the individual tourist project becomes competitive for tourism products offered on the market. Modern ICT tools supporting travel planning facilitate individual undertakings. Polish tourists’ experience based on the e-tourism applications will be presented as the report from the survey conducted among Polish Internet users. The aim of this research was to verify if IT tools supporting all phases of individual tourist projects are known and used in Poland.